(untitled) (Analysis in Theory and Applications, 2017)
In this article, we study on the existence of solution for a singularities of a system of nonlinear fractional differential equations (FDE). We construct a formal power series solution for our considering FDE and prove convergence of formal solutions under conditions. We use the Caputo fractional differential operator and the nonlinearity depends on the fractional derivative of an unknown function.